Approximation by Certain Linear Positive Operators of Two Variables - Afşin Kürşat Gazanfer; İbrahim Büyükyazıcı (Abstract and Applied Analysis)
We introduce positive linear operators which are combined with the Chlodowsky and Szász type operators and study some approximation properties of these operators in the space of continuous functions of two variables on a compact set. The convergence rate of these operators are obtained by means of the modulus of continuity. And we also obtain weighted approximation properties for these positive linear operators in a weighted space of functions of two variables and find the convergence rate for these operators by using the weighted modulus of continuity.